Assessment of Curing Exposures Effect on the Long-term Engineering Properties of Novel Lightweight Aggregate Concrete - Jannaty, Mohammad H.; Atrushi, Dawood (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
At present, most of the generated waste expanded polystyrene (EPS) in developed countries are transported to landfill and in some developing and/or less-developed countries such as Iraq are sent to open landscapes; consequently, this inadequate waste disposal can be very dangerous to our health and environment. This study describes engineering properties of sustainable lightweight aggregate concrete (LWAC) incorporating novel aggregates of waste EPS produced by a unique recycling technique of densifying. The new recycling technique significantly improved the segregation resistance of EPS beads in concrete as these beads are ultra-light material. The novel LWA of densified EPS (DEPS) was used as partial natural aggregate replacement in the mixes. Three water/cement (W/C) ratios were used. Three different types of curing conditions of indoor full water curing, outdoor weathering exposure, and heating exposure were employed during this study to represent different conditions which concrete may be subject to. The engineering properties of concrete investigated were consistency, dry density, compressive strength, and ultrasonic pulse velocity (UPV) for long-term performance of more than one-year age. It was indicated that the properties of concrete were not only primarily influenced by the employed curing conditions but the content of DEPS in the mixtures and additionally the W/C ratio had effect on the properties of concrete. However, adequate engineering properties can be achieved using an appropriate amount of DEPS with proper W/C and curing conditions.